2013
DOI: 10.1177/1476718x12466201
|View full text |Cite
|
Sign up to set email alerts
|

Least said, soonest mended?: Responses of primary school teachers to the perceived support needs of bereaved children

Abstract: Every 22 minutes in the United Kingdom, a child is bereaved of a parent, making up some 24,000 a year. An even greater number experience the loss of a grandparent. There is a limited, but growing, body of research into the impact of grief and bereavement on young children and how their support needs might be met. This article expands upon research with primary school teachers articulating something of their knowledge and experience in encountering bereaved children. The mixed methodology research includes quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…Finally, with respect to the elements useful for a grieving child or adolescent, they coincide with those found in the scientific literature: the need for compassion, concern for the child/adolescent, and making time available to talk with the child (Potts, 2013); flexibility (Heath et al, 2012); support, communication, identification, and emotional expression (Lane et al 2014); spirituality (Lee et al 2016;McEachron, 2014); care, availability, importance of communication, distraction from what is being experienced at home, kindness, understanding, facilitation of learning, and referral to other professionals 2015); and relevance of the peer group (Gerhardt et al, 2012). Some of the participants stated that they felt uncomfortable and helpless when intervening in processes of grief and loss with the students.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Finally, with respect to the elements useful for a grieving child or adolescent, they coincide with those found in the scientific literature: the need for compassion, concern for the child/adolescent, and making time available to talk with the child (Potts, 2013); flexibility (Heath et al, 2012); support, communication, identification, and emotional expression (Lane et al 2014); spirituality (Lee et al 2016;McEachron, 2014); care, availability, importance of communication, distraction from what is being experienced at home, kindness, understanding, facilitation of learning, and referral to other professionals 2015); and relevance of the peer group (Gerhardt et al, 2012). Some of the participants stated that they felt uncomfortable and helpless when intervening in processes of grief and loss with the students.…”
Section: Discussionsupporting
confidence: 65%
“…Literature shows that, even though there are authors who point out that teachers are willing to offer their help (Potts, 2013), there is generally a deep sense of discomfort when dealing with death and grief (Alisic, 2011;Mak, 2012), as well as rejection, bargaining, depression, shock, disbelief, sadness, and feelings of guilt (Mak, 2012). The teachers who have to deal with death and grief report a lack of training on this subject (Lane et al, 2014;Potts, 2013), in spite of it being a common experience. In this regard, Lytje (2018) noted that 78% of the teachers who had a specific grief protocol felt more confident in dealing with a grief experience at school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Whereas some teachers alter their plans to accommodate bereaved students, many do not make any changes at all 8 perhaps because they are unsure what would be most helpful. [12][13][14][15] Whereas some teachers alter their plans to accommodate bereaved students, many do not make any changes at all 8 perhaps because they are unsure what would be most helpful.…”
mentioning
confidence: 99%
“…Many teachers and school staff, however, do not feel adequately equipped to support grieving students. [12][13][14][15] Whereas some teachers alter their plans to accommodate bereaved students, many do not make any changes at all 8 perhaps because they are unsure what would be most helpful. A survey study of 59 teachers from across Canada found that teachers felt uncertainty in discussing death with students, but that those with previous experience or training in this area were significantly more confident dealing with such situations.…”
mentioning
confidence: 99%